Comprehensive analysis of thermoelectrical performance of an air-based photovoltaic thermal solar collector integrated with innovative gridded metal foams - Ali M. Rasham; Mohammed A. Nima (Results in Engineering, 2025)
The thermoelectrical performance of photovoltaic thermal solar air collectors (PVTSAC), integrating partial copper metal foams that occupy 20% of the air duct volume, is numerically analyzed utilizing finite element methodology. This research proposes new cooling techniques utilizing transverse metal foams (TMFs) and innovative gridded metal foams (GMFs). The accuracy of the results for the traditional system, designated to as collector (A), was validated with a prior experimental study. The most significant drop in PV temperature was observed for collector (B) and (C) at 13.089 (°C) and 15.296 (°C), respectively. Collector (B), integrated with TMFs, exhibited superior thermal, achieving the maximum additional heat gain, thermal efficiency, thermohydraulic efficiency, and overall thermal equivalent efficiency, at 348 W, 54 %, 48 %, and 91 %, respectively. While, Collector (C), integrated with GMFs, achieved the highest electrical efficiency, net electrical power, and performance evaluation factor (PEF), recording values of 14.72 %, 61 W, and 1.68, respectively. The maximal percentage enhancement in thermal efficiency for collector (B) and electrical efficiency for collector (C) was 96 % and 7.34 %, respectively. The PEF of the collector (C) integrated with first MF sample surpassed one across all mass flow rates. Compared to the MF-filled collector, the pressure losses in collectors (B) and (C) were five to seven times and nine times lower, respectively. At a mass flow rate of 0.05 (kg/s), the heat transfer coefficients of collectors (B) and (C) were nearly four to five times higher than collector (A). The collector (C) seems appropriate for application in net-zero-energy buildings.